ANTERIOR LAMELLAR MARGINAL Z-PLASTY WITH TRANSVERSE TARSOTOMY FOR MANAGEMENT OF TRICHIASIS WITH CICATRICIAL ENTROPION -A NEW SURGICAL APPROACH - Ali, Zulfiquar; Zaffar, Danish; Kazmi, Hassan Sajid; Shah, Ashfaq Ali (Journal of Ayub Medical College Abbottabad, 2012)
Background: Trichiasis is the main risk factor for corneal opacification. The primary treatment of trichiasis is surgical. Successful surgery is likely to halt the progression of corneal opacity. The aim of the study is to report the efficacy of the anterior lamellar marginal z-plasty combined with transverse tarsotomy in the management of severe trichiasis andcicatricial entropion of upper eyelid. Methods: A prospective study was carried out from January 2009 to June 2012, on 54 eyelids (44 patients) who underwent anterior lamellar marginal z-plasty with transverse tarsotomy for correction of trichiasis and cicatricial entropion involving upper eyelid with a minimum of 6 months’ follow-up. Results were classified according to the presence and location of residual trichiasis and symptoms were assessed according to a three-level subjective scale (better, worse or no change). Failure was defined as recurrent trichiasis with one or more lashes touching any part of cornea in primary position. Secondary outcomes were visual acuity and corneal opacification. Results: At the end of six month period, none of patients had any trichiatic eye lash touching the cornea in primary position (100% success). Forty-eight (88.9%) of the operated eyelids were free of trichiasis, while residual trichiasis was noticed only in 6 (11.1%) operated lids. At the end of six months, there was a significant reduction of lash burden from median of 12 trichiatic lashes from the base line to the median of 2. All the patients reported significant reduction in symptoms of irritation. Significant improvement in visual acuity (p<0.000) and reduction in the density of corneal opacity (p<0.000) was notified from the base line. Conclusion: Anterior lamellar marginal z-plasty combined with transverse tarsotomy seems to have promising surgical outcome for the correction of trichiasis and cicatricial entropion secondary to cicatricial trachoma. Keywords: Cicatricial ectropion, trichiasis, trachoma